2017
DOI: 10.1142/s0218127417500468
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Chaotic Systems with One-Line Equilibria and Their Application to Image Encryption

Abstract: This paper introduces nine four-dimensional discrete chaotic systems with one-line equilibria (DCSLE), consisting of some simple sine functions. Based on the generalized chaos synchronization (GCS) theorem, a DCSLE is used to construct an eight-dimensional DCSLE GCS system. The new DCSLE GCS system is verified by numerical simulation and then used to design a chaotic pseudorandom number generator (CPRNG). The randomness of ten 100-key streams generated by the CPRNG, two GCS-based CPRNGs, the RC4 PRNG and the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…It is noted that memristor-based systems often have a line of equilibrium points [18]. It is interesting that Chen et al have found nine discrete chaotic systems with one-line equilibria and applied them for image encryption [19]. Chaotic systems with infinite equilibria and their applications should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that memristor-based systems often have a line of equilibrium points [18]. It is interesting that Chen et al have found nine discrete chaotic systems with one-line equilibria and applied them for image encryption [19]. Chaotic systems with infinite equilibria and their applications should be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Applications of chaos have been witnessed in various areas ranging from path planning generator [4], secure communications [5][6][7], audio encryption scheme [8], image encryption [9][10][11], to truly random number generator [12,13]. Many three-dimensional (3D) autonomous chaotic systems have been found and reported in the literature [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chaotic image cryptology research has become a hotspot in the field of information security. And that includes three main research directions: First is to study the new chaotic systems which can produce cryptographic key streams [1][2][3][4][5]. The direction serves as an important application of chaos theory to give birth to the study of new chaotic systems.…”
Section: Introductionmentioning
confidence: 99%